News Episodes in Advance Level Classes - Bahrani, Taher (Richtmann Publishing, 2011)
Today, having access to audio/visual mass media programs such as TV and radio news is very easy for all the people aroundthe world. In the same line, many studies have emphasized the pedagogical values of TV and radio programs to be used in languagelearning. Accordingly, the present study tries to investigate the effect of listening to TV and radio news on improving language learners’speaking proficiency at the advance level. For this purpose, a speaking test was administered to two hundred language learners and finallysixty language learners were selected as advance language learners and randomly divided into group one and group two. During theexperiment, group one participants had exposure to TV news to work on in-and out-side the classroom. On the contrary, the participantsin group two had only exposure to a sample selected utterances extracted from different kinds of TV and radio programs rather thannews. At the end of the experiment, both groups took another sample speaking test to see whether or not any changes happened regardingtheir speaking proficiency. The results of the post-test showed that the two groups performed differently on the post-test which wasindicative of the fact that exposure to mass media news promote language learners’ speaking proficiency at the advance level.